1999
DOI: 10.1016/s0921-4534(99)00011-8
|View full text |Cite
|
Sign up to set email alerts
|

Critical currents, pinning forces and irreversibility fields in (YxTm1−x)Ba2Cu3O7 single crystals with columnar defects in fields up to 50 T

Abstract: We have studied the influence of columnar defects, created by heavy-ion (Kr) irradiation with doses up to 6·1011 Kr-ions/cm

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…1͑a͒. 7,11 In addition, a cascade of ancillary defects propagates down to the implantation length of about 13 m, as shown in Fig. 1͑b͒.…”
Section: Experiments Detailsmentioning
confidence: 98%
See 1 more Smart Citation
“…1͑a͒. 7,11 In addition, a cascade of ancillary defects propagates down to the implantation length of about 13 m, as shown in Fig. 1͑b͒.…”
Section: Experiments Detailsmentioning
confidence: 98%
“…It was earlier reported that truncated CDs ͑named hereafter as blind holes͒ and implantation of the HEHI into the HTSC materials also produce vortex pinning enhancements, especially at high temperatures and at high magnetic fields. [5][6][7] In this paper, we present a quantitative magneto-optical ͑QMO͒ imaging study of the magnetic field distribution in a high quality YBCO single crystal, which was locally irradiated in an alternating stripe pattern in order to simultaneously compare the intrinsic and the irradiation induced magnetic responses in a single sample. The cross section of the irradiated region was imaged by field emission scanning electron microscopy ͑FESEM͒ in order to elucidate the induced defect landscape.…”
Section: Introductionmentioning
confidence: 99%
“…Thin‐film samples, even epitaxial ones, are much better suited for obtaining high j c values due to their intrinsic defects, including a certain density of grain boundaries and several types of dislocations such as growth spirals . In addition, artificial, point‐like defects have been engineered including the examples of Zn‐ and Ni substitution on the copper sites in the CuO 2 planes , columnar defects by heavy‐ion irradiation , impurity (green) phase incorporation , and BaZrO 3 inclusions . The critical current densities achieved with epitaxial films are surprisingly high, up to the order of 10 8 A cm −2 , but this is more an advantage for chip‐like devices and does not solve the need for long‐distance low‐loss current transport.…”
Section: Superconducting Perovskitesmentioning
confidence: 99%
“…Though columnar defects creation needs advanced techniques these are highly suitable for enhancement of J c [13,14] and shifting of irreversibility line to higher field side [15]. Trappeniers et al studied columnar defects due to Kr ions in single crystal of Y x Tm (1Àx) Ba 2 Cu 3 O 7 which considerably enhanced J c , F p and irreversibility field [16]. 0.86 GeV Pb + ions produced continuous columnar defects that showed high J c values when the field direction coincided with tracks direction in YBCO films.…”
Section: Introductionmentioning
confidence: 99%